If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(7a + -2) + 3(6a + -5) = 8(4a + -2) + -3 Reorder the terms: 2(-2 + 7a) + 3(6a + -5) = 8(4a + -2) + -3 (-2 * 2 + 7a * 2) + 3(6a + -5) = 8(4a + -2) + -3 (-4 + 14a) + 3(6a + -5) = 8(4a + -2) + -3 Reorder the terms: -4 + 14a + 3(-5 + 6a) = 8(4a + -2) + -3 -4 + 14a + (-5 * 3 + 6a * 3) = 8(4a + -2) + -3 -4 + 14a + (-15 + 18a) = 8(4a + -2) + -3 Reorder the terms: -4 + -15 + 14a + 18a = 8(4a + -2) + -3 Combine like terms: -4 + -15 = -19 -19 + 14a + 18a = 8(4a + -2) + -3 Combine like terms: 14a + 18a = 32a -19 + 32a = 8(4a + -2) + -3 Reorder the terms: -19 + 32a = 8(-2 + 4a) + -3 -19 + 32a = (-2 * 8 + 4a * 8) + -3 -19 + 32a = (-16 + 32a) + -3 Reorder the terms: -19 + 32a = -16 + -3 + 32a Combine like terms: -16 + -3 = -19 -19 + 32a = -19 + 32a Add '19' to each side of the equation. -19 + 19 + 32a = -19 + 19 + 32a Combine like terms: -19 + 19 = 0 0 + 32a = -19 + 19 + 32a 32a = -19 + 19 + 32a Combine like terms: -19 + 19 = 0 32a = 0 + 32a 32a = 32a Add '-32a' to each side of the equation. 32a + -32a = 32a + -32a Combine like terms: 32a + -32a = 0 0 = 32a + -32a Combine like terms: 32a + -32a = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 5v^2+7v=-2 | | 20c-5=-10+25 | | 8.2x-3.7x=81 | | -v+5+6v=2(n+3) | | -(3a-3)= | | 505kg-450.25kg= | | 8y+36=3y-14 | | 1.5*2.4*e=10.8 | | 6(y+1)=-2(4y-1)+4y | | q=R-Rsx | | 18=3(2c+3) | | u+(-32)=-48 | | -5(8v-2)= | | 3.5y-5=15 | | 25n-2+42=-60 | | 2.6(x+2.5y)+4(2.5x+1.3y)= | | 7m-3=6-3m | | 2(6n-8)= | | 3(1-3x)=2(-4x-7) | | 159.98+1s=79.98+5s | | -5(v-3)=-8v+6 | | 9+24x+16x^2=0 | | 51=-7(-1+2v)+2 | | 4y+x=9x | | -(4x-7)-5x=10+x | | 159.99+1s=79.99+5s | | 12x+5+8x+17= | | 4v-28=2(v-4) | | 11x+24=x+18 | | 10=Tx+4 | | 4.4-2r=-7.8 | | 3x+6=4(2x-6) |